Bio-dye sensitized solar cell for energy conversion - Ahmed, Nafees; Mohamad, Souad A.; Othman, Raihan; Ali, Mohd Hamdi (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Dye-sensitized solar cells (DSSCs) have achieved vast popularity for being a potential alternative to silicon based solar cells as this kind of cells impose cost effectiveness, easy fabrication process, multicolor options and low energy payback time. DSSCs offer wide range of options while selecting the dye, since both the natural and chemical dyes can be used as light harvesting material which acts as the charge carriers in liquid form. Generally, TiO2 is used as the wide band gap working electrode for the charge separation and transportation. Such kind of DSSC follows close mechanism to the photosynthesis process where the natural pigments acts as the light harvesting medium. Therefore, the objective of this paper is to summarize the recent available knowledge regarding the natural dyes that have been used to assemble DSSCs ensuring sustainability, low cost mechanism, and reasonable light harvesting efficiency.